Clinical Severity of Visceral Leishmaniasis Is Associated with Changes in Immunoglobulin G Fc N-Glycosylation - Luiz Gustavo Gardinassi (American Society for Microbiology, 2014)
ABSTRACT  Visceral leishmaniasis (VL) has a high fatality rate if not treated; nevertheless, the majority of human infections with the causative agent, Leishmania infantum chagasi, are asymptomatic. Although VL patients often present with increased levels of serum immunoglobulins, the contribution of antibodies to resistance or progression to disease remains unknown. Effector and regulatory functions of antibodies rely on their interactions with type I and II Fc receptors, and these interactions are tuned by the patterns of antibody Fc N-glycosylation. In view of these facts, we applied a robust method of IgG Fc N-glycopeptide profiling of serum samples from 187 patients with VL, 177 asymptomatic individuals, 116 endemic controls (individuals residing in areas where VL is endemic) and 43 nonendemic controls (individuals living in an area where VL is not endemic). We show that, in comparison to the overall IgG Fc N-glycan profiles of asymptomatic or uninfected healthy individuals, those of patients with VL are profoundly altered. These changes correlate with levels of serum cytokines and the inflammation marker C-reactive protein. We also fitted univariate and multivariate ordinal logistic regression models to demonstrate the ability of IgG Fc N-glycosylation features and immunity regulators present in serum to predict disease severity in VL patients. Importantly, we show that Fc N-glycosylation profiles change after treatment of VL. This study introduces important concepts contributing to the understanding of antibody responses in infections with Leishmania parasites and provides new insights into the pathology of human VL. IMPORTANCE Immunoglobulins (Ig) have been shown to present pro- and anti-inflammatory functions according to the profile of carbohydrates attached to their Fc region. Glycosylation features of serum IgG have been examined in relation to several autoimmune and infectious diseases and provide a mechanistic basis for the protective or pathogenic role of antibodies. Leishmania infantum chagasi is the causative agent of visceral leishmaniasis (VL) in South America, and we show that VL patients produce IgG with patterns of Fc glycans similar to those found in other inflammatory conditions. Specific Fc N-glycosylation features and levels of serum cytokines and C-reactive protein are significantly associated with the development of severe clinical symptoms and, notably, Fc glycosylation changes after treatment. The modifications detected in the N-glycosylation features of IgG Fc from VL patients raise new perspectives on the effector or regulatory role of antibodies in immune responses elicited by infection with Leishmania parasites.